Endothelial Cells Derived from the Blood-Brain Barrier and Islets of Langerhans Differ in their Response to the Effects of Bilirubin on Oxidative Stress Under Hyperglycemic Conditions - Kapitulnik, Jaime; Benaim, Clara; Sasson, Shlomo (Frontiers in Pharmacology, 2012)
Unconjugated bilirubin (UCB) is a neurotoxic degradation product of heme. Its toxic effects include induction of apoptosis, and ultimately neuronal cell death. However, at low concentrations, UCB is a potent antioxidant that may protect cells and tissues against oxidative stress by neutralizing toxic metabolites such as reactive oxygen species (ROS). High glucose levels (hyperglycemia) generate reactive metabolites. Endothelial cell dysfunction, an early vascular complication in diabetes, has been associated with hyperglycemia-induced oxidative stress. Both glucose and UCB are substrates for transport proteins in microvascular endothelial cells of the blood-brain barrier (BBB). In the current study we show that UCB (1-40 M) induces apoptosis and reduces survival of bEnd3 cells, a mouse brain endothelial cell line which serves as an in vitro model of the BBB. These deleterious effects of UCB were enhanced in the presence of high glucose (25 mM) levels. Interestingly, the bEnd3 cells exhibited an increased sensitivity to the apoptotic effects of UCB when compared to the MS1 microcapillary endothelial cell line. MS1 cells originate from murine pancreatic islets of Langherans, and are devoid of the barrier characteristics of BBB-derived endothelial cells. ROS production was increased in both bEnd3 and MS1 cells exposed to high glucose, as compared with cells exposed to normal (5.5 mM) glucose levels. While UCB (0.1-40 M) did not alter ROS production in cells exposed to normal glucose, relatively low ('physiological') UCB concentrations (0.1-5 M) attenuated ROS generation in both cell lines exposed to high glucose levels. Most strikingly, higher UCB concentrations (20-40 M) increased ROS generation in bEnd3 cells exposed to high glucose, but not in similarly treated MS1 cells. These results may be of critical importance for understanding the vulnerability of the BBB endothelium upon exposure to increasing UCB levels under hyperglycemic conditions.